2011
DOI: 10.1051/0004-6361/201015989
|View full text |Cite
|
Sign up to set email alerts
|

The initial period function of late-type binary stars and its variation

Abstract: The variation in the period distribution function of late-type binaries is studied. It is shown that the Taurus-Auriga pre-main-sequence population and the main-sequence G dwarf sample do not stem from the same parent period distribution with better than 95 per cent confidence probability. The Lupus, Upper Scorpius A, and Taurus-Auriga populations are shown to be compatible with being drawn from the same initial period function (IPF), which is inconsistent with the main-sequence data. Two possible IPF forms ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 49 publications
7
48
1
Order By: Relevance
“…This suggests that there are no significant variations in binary-star formation depending on the ambient condition required, but that variations in the binary populations are mainly caused by stellar and dynamical evolution. This agrees with previous work and such an assumption would be similar to the universality hypothesis of the stellar IMF (Kroupa 2011;Kroupa & Petr-Gotzens 2011).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This suggests that there are no significant variations in binary-star formation depending on the ambient condition required, but that variations in the binary populations are mainly caused by stellar and dynamical evolution. This agrees with previous work and such an assumption would be similar to the universality hypothesis of the stellar IMF (Kroupa 2011;Kroupa & Petr-Gotzens 2011).…”
Section: Discussionsupporting
confidence: 93%
“…1). This distribution agrees 1 with pre-main sequence and proto-stellar multiplicity data (Kroupa & Petr-Gotzens 2011;. The period distribution is assumed to be the universal outcome of binary formation (Kroupa 2011).…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…The conclusion that the distribution for M-dwarfs in the lucky imaging results is indeed that narrow originates from the observation that the distribution starts to decline strongly far from the resolution limit of the respective surveys. This apparent continuity might however be the result of the density-dependent dynamical alteration of an environment-independent birth binary population for late-type stars in young star forming regions (Kroupa 1995(Kroupa , 2011Kroupa & Petr-Gotzens 2011;Marks & Kroupa 2012;Marks et al 2014) and the subsequent addition of many such populations originating from different environments that comprise the Galactic field (Parker et al 2009;Goodwin 2010;Marks et al 2015). In particular, the mutual proximity of BD and late-M separation distributions in Janson et al (2014) might be following from separate BD and stellar populations which underwent dynamical processing, as Marks et al (2015) have demonstrated.…”
Section: Width Of the Separation Distributions Of Galactic Field Binamentioning
confidence: 99%